SHOULD ENGLISH LESSON BE ABOLISHED AT THE ELEMENTARY SCHOOL LEVEL? ENGLISH TEACHERS’ AND PARENTS’ DILEMMA OF THE 2013 CURRICULUM - Ahmad Kosasih; Dewi Listia Apriliyanti (IKIP Siliwangi, 2020)
The 2013 curriculum has removed English subjects at the elementary school level. This resulted in the emergence of a dilemma in both the teacher and parents of students. Hence, this research was carried out for analyzing the abolished English subject at the elementary school. This study is conducted to analyze the abolished English lesson at the elementary school level. A case study is applied as this research design. Key informants of this study were English teacher who taught at one of private elementary school in Bandung, and a parent of students. The researcher found a similarty between English teacher and parent of students’, which is strongly disagree with the abolition English lesson in elementary school. Therefore, this study purposed alternative solution to resolve the abolished English lesson at the elementary school level in 2013 curriculum. Keywords: Abolished, English Lesson, Curriculum 2013